Comparison of the Pulmonary Oxidative Stress Caused by Intratracheal Instillation and Inhalation of NiO Nanoparticles when Equivalent Amounts of NiO Are Retained in the Lung - Masanori Horie; Yukiko Yoshiura; Hiroto Izumi; Takako Oyabu; Taisuke Tomonaga; Takami Okada; Byeong-Woo Lee; Toshihiko Myojo; Masaru Kubo; Manabu Shimada; Yasuo Morimoto (MDPI AG, 2016)
NiO nanoparticles were administered to rat lungs via intratracheal instillation or inhalation. During pulmonary toxicity caused by NiO nanoparticles, the induction of oxidative stress is a major factor. Both intratracheal instillation and inhalation of NiO nanoparticles induced pulmonary oxidative stress. The oxidative stress response protein, heme oxygenase-1 (HO-1), was induced by the administration of NiO nanoparticles at both the protein and gene expression level. Additionally, certain oxidative-stress markers in the lung, such as 8-iso-prostaglandin F2α, thioredoxin, and inducible nitric oxide synthase were increased. Furthermore, the concentration of myeloperoxidase (MPO) in the lung was also increased by the administration of NiO nanoparticles. When the amount of NiO in the lung is similar, the responses against pulmonary oxidative stress of intratracheal instillation and inhalation are also similar. However, the state of pulmonary oxidative stress in the early phase was different between intratracheal instillation and inhalation, even if the amount of NiO in the lung was similar. Inhalation causes milder oxidative stress than that caused by intratracheal instillation. On evaluation of the nanoparticle-induced pulmonary oxidative stress in the early phase, we should understand the different states of oxidative stress induced by intratracheal instillation and inhalation.